qual a sentença matemática da função do 2ºg que satisfaça f(-2)=0, f(2)=0 e f(0)=-1.
Soluções para a tarefa
Respondido por
1
f(-2)=0, f(2)=0 e f(0)=-1.
f(x) = ax² + bx + c
f(-2)=0 ==> a(-2)² + b(-2) + c = 0 ==> 4a - 2b + c = 0
f(2)=0 ==> a(-2)² + b(-2) + c = 0 ==> 4a + 2b + c = 0
f(0)=-1 ==> a(0)² + b(0) + c = -1 ==> 0 - 0 + c = - 1 ==> C = - 1
==================================================
4a - 2b + c = 0 ==> 4a - 2b - 1 = 0 ==> 4a - 2b = 1
4a + 2b + c = 0 ==> 4a + 2b - 1 = 0 ==> 4a + 2b = 1
4a - 2b = 1
4a + 2b = 1
8a = 2
a = 2
8
===================================================
4a + 2b = 1
4,2 + 2b = 1
8
8 + 2b = 1 ==> 1 + 2b = 1 ==> 2b = 1-1 ==> 2b=0 ==> b = 0
8
===================================================
f(x) = ax² + bx + c
f(x) = 2x² + 0x - 1
8
Perguntas interessantes
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás